Pioglitazone: an anti-diabetic compound with anti-aging properties. - Jafari, M.; Khodayari, B.; Felgner, J.; Bussel, I.I.; Rose, M.R.; Mueller, L.D. (Biogerontology, 2007)
Insulin and Insulin-Growth-Factor-like (IGF) signaling pathways are well known longevity pathways in nematodes, insects and mammals. To our knowledge, there are no systematic pharmacological studies evaluating the anti-aging properties of medications that target this pathway in Drosophila. Although there are no published data implicating an anti-aging role for these compounds in Drosophila, we hypothesized that their promising pharmacological profile might decrease mortality. However, the decrease in mortality could be due to a number of potential artifacts and confounds such as fecundity depression, decrease in metabolic rate, or CNS depression. Therefore, the mere finding that a compound decreases mortality does not qualify it as an anti-aging compound. In this study, we evaluated the anti-aging properties of four compounds that might target the insulin signaling pathway in Drosophila. Once it was established that the compound decreased mortality, we proceeded to evaluate possible confounding factors that could have contributed to the mortality reduction. We show that only piolglitazone displayed anti-aging properties. At present, we do not have a mechanistic explanation for this pharmacological disparity.